2022
DOI: 10.3389/fmicb.2022.1062763
|View full text |Cite
|
Sign up to set email alerts
|

Host diet shapes functionally differentiated gut microbiomes in sympatric speciation of blind mole rats in Upper Galilee, Israel

Abstract: The gut microbiome is important for host nutrient metabolism and ecological adaptation. However, how the gut microbiome is affected by host phylogeny, ecology and diet during sympatric speciation remain unclear. Here, we compare and contrast the gut microbiome of two sympatric blind mole rat species and correlate them with their corresponding host phylogeny, ecology soil metagenomes, and diet to determine how these factors may influence their gut microbiome. Our results indicate that within the host microbiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 98 publications
1
6
0
Order By: Relevance
“…Rather than a different evolutionary history of the hosts, different sampling seasons may also explain the differences in the relative abundance of the phyla. Another study of closely related Blind Molerat species (N. ehrenbergi) showed the exact same order of the most abundant phyla, while the relative abundances of the phyla are slightly different [45] (Table 3). The same three bacterial phyla dominate the microbiota of other rodents, such as house mice [17,46], rats [47], and naked molerats [18,48].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Rather than a different evolutionary history of the hosts, different sampling seasons may also explain the differences in the relative abundance of the phyla. Another study of closely related Blind Molerat species (N. ehrenbergi) showed the exact same order of the most abundant phyla, while the relative abundances of the phyla are slightly different [45] (Table 3). The same three bacterial phyla dominate the microbiota of other rodents, such as house mice [17,46], rats [47], and naked molerats [18,48].…”
Section: Discussionmentioning
confidence: 85%
“…The bacterial phyla Oscillospiraceae (phylum Firmicutes) and Ruminococcus (phyla Firmicutes) were the third and fourth most abundant phyla with 12% and 7% abundance, respectively. While [44] reported that these bacterial families comprised >5% of their data too (Oscillospiraceae used to categorise under Ruminococcus), [45] did not mention the abundance of bacterial families in their study. Together with the second most abundant bacterial family Lachnospiraceae, Oscillospiraceae, and Ruminococcus were found to be abundant in performance-associated hosts such as human athletes and racehorses [56,57].…”
Section: Discussionmentioning
confidence: 96%
“…The microbiome is in uenced by various factors, such as habitat variation [22], lifestyle [23], host diet [19,24,25], host phylogeny [26], reproductive status of host [27], social interactions [28,29] and environment [18, 30,31]. Among these factors, the environment holds signi cant importance as it can impact the physiology and immune responses of the host, while also playing a pivotal role in shaping dietary preferences and the selection process of the diverse pool of microbes in the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…Because host species colonization history often follows the altitudinal gradient, the genome-wide population differentiation is expected to vary with altitude. The change in altitude also affects the composition of the ecological communities [48][49][50], which in turn shape the diet of animals [19,25]. The diet stands as one of the primary factors affecting the microbiome composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation